An Effective E‑Module to Support Decision‑Making in Selecting Contraceptive Methods - Wahyu Wahyu; Sri Rejeki; Machmudah Machmudah (FORIKES, 2026)
Unintended pregnancy and inappropriate contraceptive use remain significant public health challenges among women of reproductive age. Limited access to accurate contraceptive information and inadequate counseling may hinder informed decision‑making. With the rapid advancement of digital health technologies, e‑module–based contraceptive education has emerged as a promising strategy to strengthen women’s knowledge and support informed contraceptive choices. This systematic review aimed to examine the effectiveness of e‑module–based contraceptive education in supporting informed contraceptive decision‑making among women of reproductive age. A systematic review was conducted following PRISMA guidelines. Searches were performed in PubMed, ScienceDirect, ProQuest, and Google Scholar. Eligible studies included original quantitative or mixed‑method research involving women of reproductive age, using e‑module or digital contraceptive education interventions, and reporting outcomes related to decision‑making, knowledge, attitudes, or contraceptive choice. Data were synthesized narratively. Across the included studies, e‑module–based contraceptive education consistently demonstrated positive effects on multiple dimensions of informed decision‑making. Most interventions significantly improved participants’ contraceptive knowledge, including understanding of method effectiveness, side effects, and correct use. Several studies reported enhanced attitudes toward contraceptive planning, greater confidence in evaluating available options, and increased readiness to engage in shared decision‑making with healthcare providers. Digital modules also contributed to reductions in decisional conflict, particularly by clarifying personal values and aligning contraceptive choices with individual preferences and reproductive goals. In some studies, women expressed higher satisfaction with digital learning formats due to their flexibility, privacy, and ease of access. Overall, digital contraceptive education showed comparable or superior effectiveness to conventional counseling, especially in improving comprehension and supporting autonomous decision‑making. In conclusion, E‑module–based contraceptive education effectively strengthens informed contraceptive decision‑making among women of reproductive age. Integrating digital modules into nursing practice and family planning services may enhance patient‑centered care. Further high‑quality studies are needed to assess long‑term outcomes.Keywords: contraception; decision making; digital health; reproductive health; women